Peningkatan Keterampilan Menulis Teks Eksposisi menggunakan Model Problem Based Learning (PBL) di Kelas V UPTD SDN 04 Mungka Kabupaten 50 Kota - Didriantosi, Nadilla Putri; Muhammadi, Muhammadi (Asian Journal of Early Childhood and Elementary Education, 2025)
This study was motivated by the low writing skills of fifth-grade students at UPTD SDN 04 Mungka, Kabupaten 50 Kota, which were attributed to a teacher-centered learning process. The aim of the research was to describe the improvement of students’ writing skills through the implementation of the Problem-Based Learning (PBL) model. This research employed Classroom Action Research (CAR) with both qualitative and quantitative approaches, conducted over two cycles. Cycle I consisted of two meetings, while Cycle II comprised one meeting, each involving four stages: planning, implementation, observation, and reflection. The research subjects included the classroom teacher and 20 fifth-grade students (9 boys and 11 girls). Data were collected through lesson plan assessments, observations, tests, and non-test instruments. The results showed improvements in: (a) lesson plan quality, from 85.4% in Cycle I to 95.8% in Cycle II; (b) teacher activity, from 82.14% to 96.42%, and student activity from 78.56% to 96.42%; (c) students’ writing skills, with the average score increasing from 74.4 in Cycle I to 85.96 in Cycle II. These findings demonstrate that the implementation of the PBL model effectively enhances the writing skills of fifth-grade students at SDN 04 Mungka.